Analysis and Discussion of Some Key Technical Problems for LWD Ultra-Deep Electromagnetic Resistivity Logging - JIN Ding; ZHU Jun; ZHOU John (Cejing jishu)
Ultra-deep electromagnetic resistivity logging technique and tools are currently the research hotspot of LWD. The look-around DOD (Distance of Detection), look-ahead DOD and the bed boundary resolution are important technical specifications of these type of tools, so it is vital to solve some key technical problems for developing the tools and related processing software. Based on antenna arrangement, measurement function and signal, this paper discusses the concepts and specifications of look-around DOD, look-ahead DOD and the boundary resolution, and analyzes their influencing factors by numerical simulation. The numerical simulation results show that the look-around/look-ahead DOD and the boundary resolution of the ultra-deep electromagnetic logging tool depend on the arrangement of antennas, the type of geosignal, antenna spacing, operating frequency, formation resistivity and contrast, and they also are closely related to the capability of the tools to detect weak signals. This paper also discusses the key technical problems in the research and development of the ultra-deep electromagnetic logging tools, such as the accurate detection and processing of nanovolt-level weak signals, the designing and manufacturing of inclined/orthogonal antennas resistant against high pressure, strong vibration, corrosion of hydrogen sulfide and flushing of mud & rock fragments, and the fast inversion of multi-scale data. The influence factors of these key technical problems are analyzed, and the corresponding suggestions are given as follows: for circuit designing, suppressing interference signals, enhancing strength and stability of signals, and processing with high precision. In antenna designing and manufacturing, selecting high-strength materials, improving machining accuracy, designing and adopting special crafts & tools. In terms of data inversion, improving the speed, accuracy and stability and eliminating multiple solutions. The above discussion and analyses aims to give some ideas or views to the technical personnel engaged in the research and development of LWD electromagnetic imaging logging tools and data processing.